Analisis Kompetensi, Kompensasi, Dan Pelaksanaan Good Pharmacy Practice (GPP) Terhadap Kepuasan Kerja Apoteker - Galuh Setyorini, Elisa; Rusandy, Debby Satyo; Laksono, Sonny SM (Universitas Islam Kadiri, 2023)
This study aims to examine the effect of competence, compensation, and the implementation of Good Pharmacy Practice (GPP) on the job satisfaction of pharmacists who in charge of pharmacies in Kediri Regency. Good pharmacy practice (GPP) is a standard to ensure pharmacists provide every pharmaceutical service so as to create job satisfaction. This research was conducted with a cross sectional survey design. Research uses a questionnaire as a data collection tool. The sampling technique used is non-probability sampling. The number of samples used was 97 pharmacists who had licenses to practice in charge in Kediri Regency. The results showed that there was a significant relationship between competency (p=0.015) and implementation of GPP (0.024) on job satisfaction. For compensation, it has an r-table (1,661) < r-count (1,977) which indicates that there is a significant relationship with job satisfaction. Overall, there is a significant relationship (p=0.000) with competence, compensation, and GPP implementation and has a positive effect on pharmacist job satisfaction in pharmacies in the Kediri Regency.